Mindcrafting: The Semantic Characteristics of Spontaneous Names Generated as an Aid to Cognitive Mapping and Navigation of Simulated Environments. (October 2017) - Butler, James O.
Background. This study explores the extent to which names are formed to serve the development ofmental maps to enable efficient navigation of unfamiliar terrain, conducted within a simulated landscape. Purpose. The primary aim of this study was to examine the semantic properties of spontaneous naming systems, and investigate their potential waypointing influence inpersonal route mapping . Method. Participants were tasked with the exploration of a closed-environment inMINECRAFT to find a designated goal, and return to the starting point in as short a time as possible, verbalizing their active thought process throughout. All instances of names were recorded. Results. The 12 participants created 61 names across 13 distinct sites. The environment had not been cultivated to predispose these points to be of interest, allowing a dedicated discussion of the factors that influence or are complemented by name-derived semantics. A strong negative correlation (−0.88) was found between the number ofnames generated andspeed of task completion, which was calculated to be significant. Conclusion. Name development is shown to play a role in efficientcognitive mapping, with consistent semantic developmental patterns identifiable, formed equally around interpreted poetics of a space and the observable physical form.